EFEKTIVITAS BIMBINGAN TEKNIS DALAM PENGEMBANGAN PERBENIHAN HORTIKULTURA DI JAWA BARAT - Siti Sehat Tan; Rita Indrasti (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2018)
Technical Guidance (TG) development of horticultural seedlings that took place in Bandung in October 2017 is a series of horticultural seed assistance programs, especially oranges, potatoes and mangosteen. A total of 62 horticultural seed breeders became participants in the TG. This paper aims to determine the effectiveness of TG as measured by the post-test scores, participants' appreciation of the TG implementation and changes in the level of knowledge & skills. For this reason, data is collected which includes the nominal value of the post-test, the score score of the participants' appreciation of the elements of the TG implementation which includes classical technical material, resource capabilities, infrastructure support, services, and field practice. Relevant analysis is carried out on the data collected. To test the significance of changes in test scores carried out at the beginning of the activity (pre-test) and test scores at the end of the activity (post-test), the Wilcoxon Test approach was used, while to determine the participants' appreciation for the TGimplementation using score scores approach to Likert, scale 1-5. Using this analysis, it was concluded that the implementation of TG was considered effective, as indicated by significance of changes in the positive pre-test-post-test scores, and the aspirations of participants who tended to judge good implementation of the TG. Based on the results of this study, TG can be used as an approach to improve farmers' capability in improving the performance of horticultural seed development in the future.AbstrakBimbingan Teknis (Bimtek) pengembangan perbenihan hortikultura yang berlangsung di Bandung pada Oktober 2017 merupakan rangkaian program bantuan benih hortikultura khususnya jeruk, kentang dan manggis. Sebanyak 62 orang petani penangkar benih hortikulturamenjadi peserta Bimtek tersebut.Makalah ini bertujuan untuk mengetahui efektivitas Bimtek yang diukur dari nilai post-test, apresiasi peserta terhadap penyelenggaraan Bimtek dan perubahan tingkat pengetahuan & keterampilan. Untuk itu dikumpulkan data yang meliputi nilai nominal post-test, nilai skor apresiasi peserta terhadap unsur-unsur penyelenggaraan Bimtek yang meliputi materi bimtek klasikal, kapabilitas narasumber, dukungan sarana prasarana, pelayanan, dan praktek lapangan. Terhadap data yang terkumpul dilakukan analisis yang relevan. Untuk menguji signifikansi perubahan nilai test yang dilakukan pada awal kegiatan (pre-test) dan nilai test di akhir kegiatan (post-test), dilakukan dengan pendekatan Uji Wilcoxon, untuk mengetahui apresiasi peserta terhadap penyelenggaraan Bimtek menggunakan pendekatan nilai skor mengikuti Likert, pada skala 1–5. Menggunakan analisis tersebut, diperoleh kesimpulan bahwa penyelenggaraan Bimtek dinilai efektif yang ditunjukkan oleh signifikansi perubahan nilai pre-test –post-test yang positif, dan aspirasi peserta yang cenderung menilai baik terhadap penyelenggaraan Bimtek. Berdasarkan hasil kajian ini, Bimtek dapat dijadikan sebagai pendekatan untuk meningkatkan kapabilitas petani dalam peningkatan kinerja pengembangan perbenihan hortikultura ke depan.